Diversity of NC10 bacteria associated with sediments of submerged Potamogeton crispus (Alismatales: Potmogetonaceae) - Wang,Binghan; Huang,Shanshan; Zhang,Liangmao; Zhao,Jianwei; Liu,Guanglong; Hua,Yumei; Zhou,Wenbing; Zhu,Duanwei (PeerJ, 2018)
Background The nitrite-dependent anaerobic methane oxidation (N-DAMO) pathway, which plays an important role in carbon and nitrogen cycling in aquatic ecosystems, is mediated by “Candidatus Methylomirabilis oxyfera” (M. oxyfera) of the NC10 phylum. M. oxyfera-like bacteria are widespread in nature, however, the presence, spatial heterogeneity and genetic diversity of M. oxyfera in the rhizosphere of aquatic plants has not been widely reported. Method In order to simulate the rhizosphere microenvironment of submerged plants, Potamogeton crispus was cultivated using the rhizobox approach. Sediments from three compartments of the rhizobox: root (R), near-rhizosphere (including five sub-compartments of one mm width, N1–N5) and non-rhizosphere (>5 mm, Non), were sampled. The 16S rRNA gene library was used to investigate the diversity of M. oxyfera-like bacteria in these sediments. Results Methylomirabilis oxyfera-like bacteria were found in all three sections, with all 16S rRNA gene sequences belonging to 16 operational taxonomic units (OTUs). A maximum of six OTUs was found in the N1 sub-compartment of the near-rhizosphere compartment and a minimum of four in the root compartment (R) and N5 near-rhizosphere sub-compartment. Indices of bacterial community diversity (Shannon) and richness (Chao1) were 0.73–1.16 and 4–9, respectively. Phylogenetic analysis showed that OTU1-11 were classified into group b, while OTU12 was in a new cluster of NC10. Discussion Our results confirmed the existence of M. oxyfera-like bacteria in the rhizosphere microenvironment of the submerged plant P. crispus. Group b of M. oxyfera-like bacteria was the dominant group in this study as opposed to previous findings that both group a and b coexist in most other environments. Our results indicate that understanding the ecophysiology of M. oxyfera-like bacteria group b may help to explain their existence in the rhizosphere sediment of aquatic plant.
Keywords: Nitrite-dependent anaerobic methane oxidizing; NC10 phylum; M. oxyfera-like bacteria; Rhizosphere; Submerged plant; Microbial diversity